Unsteady analysis on the instantaneous forces and moment arms acting on a novel Savonius-style wind turbine - Roy, Sukanta; Ducoin, A. (Elsevier, 2016)
This paper aims to present a transient analysis on the forces acting on a novel two-bladed Savonius-style wind turbine. Two-dimensional unsteady Reynolds Averaged Navier Stokes equations are solved using shear stress transport k-? turbulence model at a Reynolds number of 1.23 × 10 5 . The instantaneous longitudinal drag and lateral lift forces acting on each of the blades and their acting points are calculated. The corresponding moment arms responsible for the torque generation are obtained. Further, the effect of tip speed ratio on the force coefficients, moment arms and overall turbine performances are observed. Throughout the paper, the obtained results for the new design are discussed with reference to conventional semi-circular design of Savonius turbines. A significant performance improvement is achieved with the new design due to its increased lift and moment arm contribution as compared to the conventional design. More interestingly, the present study sets a platform for future aerodynamic research and improvements for Savonius-style wind turbines.